The Slippery Slope from Pluralistic to Plural Societies - Nicola Campigotto; Chiara Rapallini; Aldo Rustichini (Global Labor Organization (GLO), 2021)
Academic consensus about normative prescriptions on the ethnic and cultural composition of societies has been shifting in recent decades. It has evolved from what seemed desirable but was acknowledged to be unrealistic (the noble idea of a melting pot), to what is realistic because it has already happened, but might be undesirable in the long run: the multicultural diaspora. Plural societies, an unintended consequence of multiculturalism, lurk in the background. Thus scholars of social and economic questions, as well as societies, face a threehorned dilemma. We throw some light on the dilemma by examining school friendship networks in five European countries with recent immigration. Our results highlight the force of elective affinities in overcoming differences, but they also point to the countervailing forces of elective discordance that are currently driving increasing division.
Keywords: D85; J15; Z13; 330; Friendship; Homophily; Immigration; Networks; Social cohesion